BCG Matrix Indonesia Food Industry: Strategy PT. Rajawali Nusantara Indonesia (Persero) - Miftah Fauzi; Popy Rufaidah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this research is to find out the position of companies in the food industry in Indonesia and recommend alternative strategies that can be applied to enhance the company’s performance. PT Rajawali Nusantara Indonesia (Persero) or RNI based on the BCG (Boston Consulting Group) matrix approach. This study uses a case study research method which functions to reveal factual, structured and accurate information about the research object. This study maps company performance based on growth and relative market share which is mapped through the BCG matrix to determine the company's position in the quadrants, so that it can produce alternative strategies that the company can use. The research results show an alternative position for the company in the question marks quadrant which indicates the company is in the growth stage, market share is still low and requires large funds for growth and increasing its market share. The proposed recommendation is to increase the Intensive strategy (market penetration, market development, or product development) or sell it.